Organotins in Neuronal Damage, Brain Function, and Behavior: A Short Review - Ferraz da Silva, Igor; Freitas-Lima, Leandro Ceotto; Graceli, Jones Bernardes; Rodrigues, Lívia Carla de Melo (Frontiers in Endocrinology, 2018)
The consequences of environmental contaminants exposure have shown important effects in brain function and behavior in different experimental models. Among the various classes of pollutants with potential neurotoxic properties, the endocrine disrupting chemicals (EDC), such as organotins (OTs), have received special attention, due to their toxic effects on the central nervous system by causing abnormal mammalian neuroendocrine axis function. OT compounds are organometallic pollutants with a tin atom bound to one or more carbon atoms. OT exposure may occur through the food chain or contaminated water, since they have multiple uses in the industry and agriculture. In addition, OTs have been used without any legal restrictions in the last decades, despite being highly toxic. Besides their action as EDC, interfering in the pathways of synthesis, release and metabolism of hormones, OTs can also cross the blood-brain barrier and show relevant neurotoxic effects, as shown in several studies in animal models. The neurotoxicity of environmental chemicals, especially the ones that act like EDC, can lead to the development of neurodegenerative processes. The aim of this short-review is to summarize the toxic effects of the most common organotin compounds, as trimethyltin (TMT), tributyltin (TBT), triethyltin (TET) and triphenyltin (TPT) on the brain function and behavior, with a focus on the neuronal damage caused by oxidative stress, neuroinflammation, alteration in cellular function and the disruption of neuroendocrine pathways as well.